Globalisasi : Krisis Identitas Dan Bela Negara Pada Generasi Muda - Muhammad Ramadhan Nawawi Kurniawan; Hapyla Dharen; Safhira Rajibah; Adha Syarief (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Globalisation occurs due to advances in technology and science. One of the benefits of globalisation is the easy access to information and news around the world, but not all news and information obtained is good and true source. Especially in the younger generation who use gadgets in their daily lives, making things that need to be watched out for. Because if the younger generation is accustomed to everything that happens on the internet, it will have an impact on attitudes and behaviour. This must be watched out for, because it is related to the identity and attitude of state defence embedded in the younger generation. Thus, this research was conducted to find out the extent of the impact of globalisation on the identity and attitude of state defence in the younger generation. The research was conducted using quantitative methods, with a total of 50 respondents, consisting of 28 women, 22 men and are the nation's young generation with an age range of 15-25 years. From the results of the research conducted, it is known that there are still many young people who are aware of the importance of maintaining identity and state defence.